Financial literacy to develop complex thinking skills: quantitative measurement in Mexican women entrepreneurs - Bayly-Castaneda, Karla; Ramírez-Montoya, María Soledad; Erdély-Ruiz, Arturo; Montoya-Bayardo, Miguel Angel (Frontiers in Education, 2024)
The objective of the study was to validate the construction of a financial literacy measurement instrument aligned with complex thinking competencies in Mexican women entrepreneurs. By means of the construct validation method, the content was validated by expert judgment, validation by exploratory and confirmatory factor analysis, as well as internal consistency by means of a pilot test applied to a sample of 189 participants. A highly valid and reliable version was obtained, organized in four dimensions with a total of 23 items. This study examines and estimates the determinants of financial literacy for the first time under the light of complex reasoning.